The corporate whistleblower's survival guide : a handbook for committing the truth - Devine, Tom, 1951- (BK currents book., 2011)
Overview: From Erin Brockovich to Enron, whistleblowers who "challenge abuses of power that betray the public trust" have proven to be an unfortunate necessity in modern business culture. Their efforts to report crimes, fraud, and dangers to public health and safety have saved millions of lives and billions of dollars of shareholder value-and had we heeded the warnings of whistleblowers, perhaps disasters such as the Bernie Madoff scandal and the Lehman Brothers meltdown could have been averted. Recent federal legislation in finance and health reform have cemented legal protections and mechanisms for whistleblowing. This book provides a thorough guide and history to the whistleblower's legal rights. The ultimate survival guide, it provides advice on getting help and finding allies, warns that retaliation is often the reward for "committing the truth" and shows how to weather the storm. With extensive legal texts, sample letters, resources, and information on upcoming whistleblower reforms, this is the ultimate source on the subject.